2009
DOI: 10.1128/cvi.00355-08
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Purified Antigens for Serodiagnosis of Pulmonary Tuberculosis: a Meta-Analysis

Abstract: The failure to diagnose tuberculosis (TB) accurately and rapidly is a key challenge in curbing the epidemic (45,88,116). Sputum microscopy, currently the sole diagnostic test in most areas where TB is endemic, has several limitations; in particular, the sensitivity compared with that of culture is variable (80,97,104,116), multiple patient visits are required (56,93,114), considerable technical training is necessary, and the procedure is labor-intensive (45, 65). Antibody detection tests (serological tests) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 99 publications
11
137
0
3
Order By: Relevance
“…Another metaanalysis, conducted in 2009, evaluated the performance of serological tests for pulmonary TB. (22) In 25 studies, the mean sensitivity was found to be 40% (range, 10-90%), and the mean specificity was 96% (range, 48-100%). These values are similar to those found for the test in serum in the present study, i.e., 30% (95% CI: 16-49) and 84% (95% CI 74-83), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another metaanalysis, conducted in 2009, evaluated the performance of serological tests for pulmonary TB. (22) In 25 studies, the mean sensitivity was found to be 40% (range, 10-90%), and the mean specificity was 96% (range, 48-100%). These values are similar to those found for the test in serum in the present study, i.e., 30% (95% CI: 16-49) and 84% (95% CI 74-83), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major fraction of secreted proteins in the MTB culture filtrate and cell wall. A relatively higher sensitivity in HIV-positive tuberculosis patients (62%) than HIV-negative tuberculosis patients (53%) with a high specificity (>95%) in both groups were reported for Ag85B (Steingart et al, 2009). MPT51 is an antigen also related to the protein family of Ag85 complex.…”
Section: Serodiagnostic Markersmentioning
confidence: 99%
“…Since enhancement of B cell immunity and production of antibody along with protective cell-mediated immunity may play an important role in the immunopathogenesis of tuberculosis, detection of specific antibodies against various mycobacterial derived antigens could also play a significant role in the diagnosis of tuberculosis. The value of various mycobacterial native or recombinant protein, lipid or different combinations of purified antigens or commercially available kits as a potential candidate of active tuberculosis sero-marker was evaluated by the ELISA method in many attempts (Abebe et al, 2007;Verma & Jain, 2007;Steingart et al, 2009). Development of a serological test with sufficient diagnostic efficacy for tuberculosis diagnosis could be very much useful tool in resource-limited countries, as the procedures are simple, relatively cost effective and can be performed rapidly.…”
Section: Serological Diagnosis Of Tuberculosismentioning
confidence: 99%
“…Some of these antigens have been employed in developing commercial serological TB tests (8). Clinotech TB Screen from Clinotech Diagnostics and Pharmaceuticals, Inc, Canada, is one of such tests being distributed in several developing countries including Nigeria.…”
Section: Rapidmentioning
confidence: 99%